"The main female characters in the novel "Vanity Fair» by William Thackeray (Journal of Pedagogical Inventions and Practices, 2023)
The article presents the life of two women: Emily Sedley, as well as her friend and at the same time rival – Rebecca sharp. Describing the life path of each of the girls, Thackeray shows in his work, and in life as well, how cruel the confrontation of good and evil is. He recognizes not only good-nature, meekness, and love for one's close person, but also hypocrisy, self-interest, vanity, and selfishness, since they are inseparable from human life. In the novel" vanity Fair", good and evil are in a state of balance, neither force wins. Thus Thackeray makes the reader understand the following: as long as good and evil are engaged in a fierce struggle, life on earth continues